First results about recovery of walking function in patients with intensive care unit-acquired muscle weakness from the General Weakness Syndrome Therapy (GymNAST) cohort study. Issue 12 (23rd December 2015) - Mehrholz, Jan; Mückel, Simone; Oehmichen, Frank; Pohl, Marcus
Abstract : Objectives: To describe the time course of recovery of walking function and other activities of daily living in patients with intensive care unit (ICU)-acquired muscle weakness. Design: This is a cohort study. Participants: We included critically ill patients with ICU-acquired muscle weakness. Setting: Post-acute ICU and rehabilitation units in Germany. Measures: We measured walking function, muscle strength, activities in daily living, motor and cognitive function. Results: We recruited 150 patients (30% female) who fulfilled our inclusion and exclusion criteria. The primary outcome recovery of walking function was achieved after a median of 28.5 days (IQR=45) after rehabilitation onset and after a median of 81.5 days (IQR=64) after onset of illness. Our final multivariate model for recovery of walking function included two clinical variables from baseline: the Functional Status Score ICU (adjusted HR=1.07 (95% CI 1.03 to 1.12) and the ability to reach forward in cm (adjusted HR=1.02 (95% CI 1.00 to 1.04). All secondary outcomes but not pain improved significantly in the first 8 weeks after study onset. Conclusions: We found good recovery of walking function for most patients and described the recovery of walking function of people with ICU-acquired muscle weakness. Trials registrations number: Sächsische Landesärztekammer EK-BR-32/13-1; DRKS00007181, German Register of Clinical Trials.